The Dutch practice of euthanasia and assisted suicide in patients suffering from psychiatric disorders: a qualitative case review study - Bosma, Fenne; Mink, Kelly Romana; van Delden, Johannes Jozef Marten; van der Heide, Agnes; van de Vathorst, Suzanne; van Thiel, Ghislaine Jose Madeleine Wilhelmien (Frontiers in Psychiatry, 2024)
Importance: Euthanasia or assisted suicide (EAS) in patients suffering from a psychiatric disorder (PD) is a controversial topic worldwide. In the Netherlands, this practice is regulated by law. All cases of EAS have to be reported and are assessed by the Regional Euthanasia Review Committees (RTEs), who publish a selection of all cases on their website. Objective: To provide insight into the Dutch practice of EAS in patients suffering from a psychiatric disorder. Design, setting and participants: We performed a retrospective case review study in which all published cases of EAS in patients suffering from a PD between 2017 and 2022 were analyzed. Intervention(s) or exposure(s): Not applicable Main outcome(s) and measure(s): Characteristics of patients who died by EAS because of suffering from a PD, characteristics of the reporting physician and consultant(s) and the RTEs assessment of published cases. Results: Of the 72 cases studied, the majority of patients were female (n=48, 67%), suffered from 3 or more conditions (n=38, 53%) and died by euthanasia instead of assistance in suicide (n=56, 78%). In 63% of cases (n=45), the life termination was performed by a physician from the Euthanasia Expertise center (EE). The RTEs’ judgement that the case did not meet the due care criteria (n=11) was in all cases related to issues regarding the (advice of the) independent physician or psychiatric expert. Conclusion and relevance: This qualitative study shows that the RTEs attach great importance to a careful evaluation procedure of physicians handling EAS requests and to the physician demonstrating ability to reflect on his views, especially when the independent consultant evaluates the case different than the physician. Training for physicians and more transparency in the assessment of EAS requests in patients with a PD may lower the threshold for physicians to handle requests of these patients themselves. Trial registration: Not applicable.